Russin i kakan i Jesper Swedbergs Swensk Ordabok - Holm, Lars (Nordiske Studier i Leksikografi, 2012)
Among some men of linguistic distinction in Sweden, there is or rather used to be an ambition to revive words that have more or less fallen into disuse. Whenever such an attempt has been made the idea has been to make the language pithy and more vivid, more Swedish as it were. Among these men should be mentioned Stiernhielm (17th century), Spegel (18th century), Rydberg (19th century) and Collinder (20th century). However, none of them were particularly successful in their puristic efforts. Reading and editing Swensk Ordabok tempted me to make a 21st-century endeavour in the genre. The words I have picked out belong in the semantic spheres of conversation; thought, knowledge, scholarship; people (ordinary people, professional people and social outcasts); food and eating. The essay hovers on the borderline between being serious and joking.